y=-1/4(-4)-6

Simple and best practice solution for y=-1/4(-4)-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=-1/4(-4)-6 equation:


y=-1/4(-4)-6

We simplify the equation to the form, which is simple to understand
y=-1/4(-4)-6

Simplifying:
y=-0.25*(-4)-6

Reorder the terms in parentheses
y=+(+1)-6

Remove unnecessary parentheses
+y=+1-6

We move all terms containing y to the left and all other terms to the right.
+1y=+1-6

We simplify left and right side of the equation.
+1y=-5

We divide both sides of the equation by 1 to get y.
y=-5

See similar equations:

| 8x+13=53 | | 72=-8(r-2) | | a-b=7 | | 3.7x-8.5=13.7 | | y=-1/4(5)-6 | | 2x^2+27x-7.5=0 | | 6x-2=-32 | | 5=3(x-2)-(x-7) | | 2m+12=3m-21 | | -4a-5=-9 | | 2=(4x-2)(2-x) | | 3x^2+x-9=0 | | -2+4x=10 | | -3(x-4)=57 | | 2x(x+1)+x=1-2x^2 | | 5=-(-z+3) | | 7x-7=4x-7 | | 2(10+n)=48 | | (Y-6)-(y+7)=8y | | 7(p+7)-4(9+p)=12 | | 2.8p=11.2 | | -(x-8)=16 | | 102=-2+8n | | -2-6x=-74 | | 10+9m=55 | | 8z^2-8z+2=0 | | 3(5+a)=-9 | | 12(3x-3)=3(12x+6) | | -176=-8(x+9) | | -4(-2y-5)+5=97 | | 9x^2-28x+20=0 | | -4(5p+2)-47=3(4p+3) |

Equations solver categories